الدعم المغربي للثورة الجزائرية من خلال مجلة دعوة الحق المغربية 1957-1962 - نفيسة الاخضاري; د/ محمد يزير (جامعة عمار ثليجي الاغواط, 2024)
When the“ Daawat El Hak “ Magazine was founded, till the year of the independence of Algeria in 1962, that latter played a major role in supporting the Algerian Revolution which was fighting against the French colonialism. This magazine was published regularly by the Moroccan Ministry of Endowments and Islamic Affairs. It was considered as a significant platform that conveys the suffer of the Algerian people and their struggle for getting the independence. The most important aim that the Algerian revolution was trying to achieve is to be completely independent and free from French colonialism. Furthermore, Algerian fighters were seeking to establish an independent country. Their major demands were to end this colonialism and give the lands seized by the French authorities back to their legal owners from Algeria. After the Moroccan government got its independence from France in 1956, it was considered one of the very first countries that supported Algeria at the political and media levels. after all, it was the media who played a pivotal role in supporting Algeria. Concerning what was the most important things mentioned in the magazine, we mention the following few points : • Emphasizing the legitimacy of the Algerian regime. The magazine also included political and legal analyses that emphasized the people’s right to independence, so, this contributed to attract the international support. • The magazine urged readers to provide moral and material support to the Algerian warriors, and published stories and personal life experiences about the Algerian's struggle, which strengthened the fraternal ties between the two nations. • The magazine presented literary and poetic writings dealing with struggle and resistance, highlighting the role of culture in strengthening the national spirit and supporting the revolution that seeks freedom.